Chimerica: Disorienting Politics - Fan Yang; Kathalene Razzano; Delores B. Phillips; Mark Tseng-Putterman; Marcus Breen (Lateral)
Delores Phillips and Cultural Studies Association’s Globalization and Culture Working Group Co-Host Kathalene Razzano discuss Disorienting Politics: Chimerican Media and Transpacific Entanglements (University of Michigan Press, 2024) with author Fan Yang, along with writer and historian Mark Tseng-Putterman. This podcast is accompanied by a scholarly commentary by Marcus Breen.